Extraction and Characterization of Bioactive Compounds from Prunus Spinosa L. Fruits with Potential in the De-velopment of Edible Films - Oana NEGREAN; Anca FĂRCAȘ; Sonia SOCACI; Călina CIONT; Mădălina MEDELEANU; Elemer SIMON; Oana POP (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca: Food Science and Technology, 2023)
Prunus spinosa L., commonly known as blackthorn, is rich in bioactive compounds such as flavonoids, anthocyanins, phenolic acids, vitamins, minerals, and organic acids, displaying strong antioxidant and antibacterial properties. This investigation aims to assess bioactive compounds in fresh and lyophilized blackthorn fruits and analyze ethanolic extracts for phenolic content, antioxidant activity, and antimicrobial effects. The primary objective was to develop a chitosan-based film with antimicrobial and antioxidant properties, targeting the enhancement of food packaging solutions, along with inhibition of S. aureus bacteria. Results showed that ethanolic extracts of blackthorn possess significant antimicrobial efficacy, demonstrating notable effectiveness against S. aureus. Notably, the film incorporating an 80% ethanolic extract demonstrated greater effectiveness against S. aureus-inoculated cheese.  This outcome underscores the inhibitory potential of blackthorn extracts on S. aureus  growth within a food matrix.